2019
DOI: 10.1002/mrm.27942
|View full text |Cite
|
Sign up to set email alerts
|

Natively fat‐suppressed 5D whole‐heart MRI with a radial free‐running fast‐interrupted steady‐state (FISS) sequence at 1.5T and 3T

Abstract: Purpose To implement, optimize, and test fast interrupted steady‐state (FISS) for natively fat‐suppressed free‐running 5D whole‐heart MRI at 1.5 tesla (T) and 3T. Methods FISS was implemented for fully self‐gated free‐running cardiac‐ and respiratory‐motion‐resolved radial imaging of the heart at 1.5T and 3T. Numerical simulations and phantom scans were performed to compare fat suppression characteristics and to determine parameter ranges (number of readouts [NR] per FISS module and TR) for effective fat suppr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The LIBRE pulse was compared to a 1‐2‐1 WE pulse that was available on the scanner, and, apart from an RF excitation angle optimization, no further optimization of this pulse was performed. Recent work has demonstrated that fast interrupted steady‐state (FISS) can be exploited for fat‐saturated 5D free‐running cardiac imaging, and a comparison with the present approach would be very instructive. The reconstruction pipeline, including regularization weights, was identical for LIBRE, SP, WE, and IFR, although optimal regularization weights are expected to vary as each acquisition will have slightly different noise levels and residual aliasing.…”
Section: Discussionmentioning
confidence: 99%
“…The LIBRE pulse was compared to a 1‐2‐1 WE pulse that was available on the scanner, and, apart from an RF excitation angle optimization, no further optimization of this pulse was performed. Recent work has demonstrated that fast interrupted steady‐state (FISS) can be exploited for fat‐saturated 5D free‐running cardiac imaging, and a comparison with the present approach would be very instructive. The reconstruction pipeline, including regularization weights, was identical for LIBRE, SP, WE, and IFR, although optimal regularization weights are expected to vary as each acquisition will have slightly different noise levels and residual aliasing.…”
Section: Discussionmentioning
confidence: 99%
“…All data were binned and reconstructed using the following two strategies: 2.1.1 | Respiratory-resolved 5D reconstruction Prior 5D flow methods focus on resolving respiration as the 5th dimension. 18,19,21,23,27 This respiratory-resolved reconstruction scheme was based on strategies reported in a number of prior studies. 21,27,28 Data were binned into a cardiac timepoint-and respiratory-resolved 5D flow data set (kx-ky-kz-flow-cardiac-respiration).…”
Section: D Flow Acquisition and Reconstructionmentioning
confidence: 99%
“…Recent explorations into multi-dimensional and self-gated imaging have pushed the boundaries of "conventional" cardiac imaging towards more efficient scan times and operator ease-of-use. [14][15][16][17][18][19][20][21][22][23][24] Recently, a fully self-gated free-running 5D flow framework was introduced. 19,21,23,25,26 This framework featured a continuous, free-running, 3D radial sequence, with interleaved three-directional velocity encoding as well as inherent self-gating projections to encode cardiac and respiratory motion without external gating signals.…”
Section: Introductionmentioning
confidence: 99%
“…4) are also available options for fat suppression on coronary MRA. Another approach to fat suppression, the fast interrupted steady-state (FISS) sequence, uses an RF excitation pulse to natively suppress the fat signal without the need for periodical application of fat suppression and ramp-up pulses, and is reported to present a strong suppression of pericardial fat signal [60,61]. The fat suppression technique is more challenging in radial imaging with higher magnetic field strengths, since the field inhomogeneities are typically accentuated.…”
Section: Non-contrast Vs Contrast-enhanced Coronary Mramentioning
confidence: 99%